2019
DOI: 10.1186/s12876-019-1033-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human herpesviruses in biliary fluid and their association with biliary complications after liver transplantation

Abstract: Background Beta-herpesviruses are common opportunistic pathogens that cause morbidity after liver transplantation (LT). Methods Objective of the study was to evaluate the prevalence and correlation of herpesviruses in bile, blood and liver tissue and to investigate their association with biliary complications and retransplantation (re-LT) free survival after LT. The study design is a single-center case-control study. We performed quantative polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…This overall prevalence is consistent with reports from other studies 15,18 but lower than rates reported in previous works conducted in other geographical areas, including Mexico with 20% 19 and Germany with 16.4%. 20 Consistent with many other results, 10,16,21 the detection rates of CMV (6.6%), HHV6 (2.6%), and HSV (0.2%) were relatively low.…”
Section: Discussionsupporting
confidence: 84%
“…This overall prevalence is consistent with reports from other studies 15,18 but lower than rates reported in previous works conducted in other geographical areas, including Mexico with 20% 19 and Germany with 16.4%. 20 Consistent with many other results, 10,16,21 the detection rates of CMV (6.6%), HHV6 (2.6%), and HSV (0.2%) were relatively low.…”
Section: Discussionsupporting
confidence: 84%
“…The indirect adverse effect of HHV‐6 infection on liver transplantation has been studied. HHV‐6 positivity in blood or bile was associated with the incidence of liver allograft rejection 10‐12 . In liver transplantation recipients, HHV‐6 infection also results in increased risks of severe opportunistic infections, including CMV, EBV, VZV, mycobacterial disease, and invasive fungal infections 3,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of prevalence of CMV in bile ducts is part of recent investigations. 19 Halme et al reported that CMV infection is a risk factor for the development of biliary complications after LT, 20 and Gotthardt et al found that CMV DNA was detected more frequently in the bile of LT patients with nonanastomotic biliary lesions. 21 CMV was also reported to be a risk factor for the recurrence of PSC after living-donor LT. 22 Even though the correlation between CMV and biliary complications has not been confirmed in all studies and is controversial, [23][24][25] there still is increasing evidence of an association between CMV and biliary diseases, an association that was confirmed in the present study.…”
Section: Risk Of CMV Infection Without Defined Immunosuppression (%) P Valuementioning
confidence: 99%